ANALYSIS OF THE EFFECT OF ISTIGHFAR DHIKR TO ADOLESCENT ANXIETY AT BETA WAVE ACTIVITY USING ELECTROENCEPHALOGRAM (EEG) EXAMINATION - Alvania Nabila Tasyakuranti; Heni Sumarti; Hamdan Hadi Kusuma; Istikomah Istikomah; Irman Said Prastyo (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2022)
Information related to deviants in the near future is often the case by a group of adolescents. Behavior that deviates from anxiety because of a problem in daily life. One way that is taught by Islam by listed in the Qur'an and hadith to reduce anxiety in a person is to do istighfar dhikr. Knowing the beta brain wave activity in anxiety and istighfar dhikr condition can be done using an EEG (Electroencephalogram). Beta waves are brain waves that are detected when a person feels anxious. Beta wave measurement method is calculated based on peaks or troughs per second on the beta signal type frequency (13-30Hz). The method in this research is an experiment with quantitative data collection. The sample used in this study were 8 students in Universitas Islam Negeri Walisongo Semarang with an age range of 20-23 years. The data analysis technique used is bivariate with Paired T-test. The results showed that the average beta wave in anxiety condition was 14.213 Hz and istighfar dhikr was 13.085 Hz. The result of the Paired t-test showed that p = 0.002 (p 0.05) indicating that the decrease in beta waves in the brain is very significant. It shows that istighfar dhikr can reduce anxiety in adolescents.